PENERAPAN MODEL KOOPERATIF JIGSAW UNTUK MENINGKATAN HASIL BELAJAR IPA MATERI SISTEM GERAK MANUSIA PADA SISWA KELAS VIII G DI SMP NEGERI 6 JEMBER TAHUN PELAJARAN 2016/2017 - Sumarjono Sumarjono (FKIP Universitas Jember, 2018)
Teaching and learning strategies with the jigsaw cooperative model, namely the teaching and learning process consisting of several students who are members of a group who are responsible for mastering the material being taught in the hope of transmitting it to other students / friends who are still in the group. The purpose of this study is to Improving the learning outcomes of Human Motion System Material for Class VIII G students of SMP Negeri 6 Jember using the jigsaw cooperative learning strategy. This research method uses a qualitative approach, this type of research is a type of classroom action research (PTK). Class action in this study was carried out with 2 cycles. Each cycle carried out the improvements to be achieved through the reflection stage. The results showed that by taking research subjects at SMP Negeri 6 Jember class VIII G. From the results of the test results of teaching and learning in cycle 1 obtained results with an average of 65.53% while in cycle 2 an average of 74.47%